The role of experiential learning in the adoption of best land management practices. (June 2021) - Okumah, Murat; Martin-Ortega, Julia; Chapman, Pippa J.; Novo, Paula; Cassidy, Rachel; Lyon, Christopher; Higgins, Alex; Doody, Donnacha
Abstract: Agriculture is both the cornerstone of global food security and one of the main drivers of environmental degradation. To address existing and potential environmental impacts of agriculture, policymakers are increasingly focussing on influencing farmers' behaviour to adopt best management practices (BMPs). One of the strategies adopted is the provision of advice aimed at raising awareness of environmental pollution and mitigation measures. By improving farmers' awareness, it is expected that changes in behaviour would be reflected in the adoption of BMPs. This expectation is based on the assumption of a direct link between awareness and uptake of BMPs. So far, however, the limited empirical research has shown that, while there is a link between awareness and adoption, this link is indirect and is mediated and moderated by other factors. One of the potential intervening factors that remains poorly understood is the enabling capacity that experiential learning brings. Through a mixed-methods approach, we explored farmers' awareness and the role of experiential learning in the adoption of BMPs. The study focusses on the experiential learning process associated with the use of nutrient management plans to reduce diffuse water pollution from agriculture in the context of a soil sampling scheme in Northern Ireland (UK). Overall, we found that while advice seems to have contributed to increased uptake of BMPs, likelihood of adoption increased if the farmers had prepared the nutrient management plans themselves. This shows the critical role that experiential learning plays in deepening farmers' understanding and increasing the likelihood of adopting BMPs. This provides support for the conceptual premise that while information provision is important, farmers need to actively engage in and be able to reflect on the practice for it to lead to behavioural changes. The role of experiential learning also suggests the need to move from the predominant model of a unidirectional relationship (the notion that the relationship always starts from awareness to behaviour), to a bidirectional one (i.e. from behaviour to awareness) and such interactions need to be understood through analysing the feedback loops over time. More research on this could offer insights into effective ways to help farmers adopt BMPs and ultimately contribute to reducing the environmental impacts of agricultural land management. Highlights: Provision of advice aimed at raising awareness on environmental pollution and mitigation measures is gaining prominence. We explored farmers' awareness and the role of experiential learning in the adoption of BMPs. Advice contributed to uptake of BMPs, but adoption increased if farmers prepared their own nutrient management plans. Farmers need to actively engage in and be able to reflect on the practice for it to lead to behavioural changes.